Pengaruh jarak tanam dan penggunaan pupuk hayati terhadap pertumbuhan dan hasil tanaman bawang merah (Allium ascalonicum L.) Varietas Bali Karet - Miftah Dieni Sukmasari; Ita Yulianti; Adi Oksifa Rahma Harti (Fakultas Pertanian Universitas Majalengka, 2023)
This study aims to analyze the interaction of plant spacing and use of biological fertilizers on the growth and yield of shallot (Allium ascalonicum L) and analyze one or more spacing and doses of biological fertilizers that have a better effect on the growth and yield of shallot (Allium ascalonicum L.). This research was conducted in the experimental land of the Gunung Sari farmer group in Sukasari Kaler Village, Agrapura District, Kab. Majalengka. This study used a factorial randomized block design (RAK) method with 12 treatments, each treatment repeated 3 times. Differences in the effect of treatment were tested with the F test at the 5% level. When F hits > F table, then the test is continued to determine the effect between treatments that cause differences in diversity with Duncan's multiple range test at the 5% level. The results showed that all spacing treatments without the application of biological fertilizers gave the lowest results for all observed variables, both growth and yield variables. While the best results were shown by the application of biological fertilizers at a dose of 75 grams for all spacing applications, both spacing of 10 cm x 15 cm, 10 cm x 20 cm or 10 cm x 25 cm on the average of the observed variables.